The Relationship between Initial Public Offering Costs and Underpricing in the South African Equity Market - Oluwasona, Oluwatobi Christopher (My University, 2011)
The study examines the relationship between the costs of initial public offerings (IPOs) and IPO underpricing within the South African IPO market. The sample consists of 59 firms which listed on the Main Board of the JSE Securities Exchange (JSE) between 1994 and 2007. The study focuses on one main question: Is there a positive relationship between the costs of IPOs and IPO underpricing in the South African equity market? An IPO is characterised by a high degree of risk due to less public historical information, no secondary trading and changing ownership structure. An IPO process with high risks and uncertainties leads to high transaction costs of the IPO. The IPO issuing firm compensates for the high risks in the IPO process by issuing the IPO at a discount to the investing public. Relying on the changing risk hypothesis of underpricing, it is hypothesized that high costs of IPOs entails high IPO underpricing. The results of this study support the findings of previous studies that IPOs, on average, are overpriced, but find no evidence that a significant positive relationship exits between underpricing and costs. Several studies indicate that economic reforms spawn hot market IPO periods. The findings of the present study corroborate this assertion. Previous IPO studies reveal that IPOs cost less in hot market periods than in cold market periods. This is however inconsistent with the results of this study. Furthermore, the present study explored if underpricing differs for different industries. The results are consistent with those of previous research that underpricing is lower in recession-proof industries than in non recession-proof industries. The avoidance of liquidity risk is a major driver of IPO activities and IPO issuing firms
MBA - WBS
Keywords: Initial Public Offerings; Equities, South African